SURGICAL CARE AT PRIMARY HEALTH: ENHANCING SURGICAL SERVICE DELIVERY AT PRIMARY HEALTHCARE FROM GENERAL SURGEONS’ PERSPECTIVES - Chin, Ri Wei Andrew; Tan, Huan Lee; Jefry, Nur Shahkinna binti Mohd; Nurshafinaz binti Hj. Abu Bakar; Arumugam, Pathman; Dhanaraj, Prabakaran (Malaysian Journal of Public Health Medicine, 2025)
As the burden of surgical diseases increased, it sheds light onto the importance of multitier approach to deliver the essential surgical care to the public via means of primary care approach. This study aims to explore surgical conditions and its care which could be incorporated into the primary health care system. This is a qualitative study based on grounded theory model, implemented through in-depth individual interview among general surgeons in Kota Kinabalu, Sabah. Transcribed verbatims were thematically analysed manually via inductive approach. A total of 13 general surgeons had been interviewed to thematic saturation from August until October 2023. In total, 688 interview excerpts had been obtained which 5 main themes emerged were “Screening”, “Awareness”, “Treatment and Referral”, “Guided Surgical Care” and “Procedures”. Screening for malignant surgical diseases has been well established in Malaysia's public primary healthcare system. However, despite efforts to manage risk factors, screening for benign surgical conditions remains insufficient. Where cancer symptoms awareness tailor preventive efforts to reduce cancer burden, the awareness for recognition of cancer associated symptoms are still low among Malaysians. General surgeons are in favour of structured referral pathways through established cluster system via liaison officers for surgical conditions of different urgencies, in congruent with the enhanced primary health care initiative by Ministry of Health Malaysia. Surgeons also believed that ambulatory surgical procedures and non-operative surgical care could be instituted by primary healthcare team with proper credentialed training, thereby improving surgical care access to the rural populations.